2014
DOI: 10.3174/ajnr.a4140
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility-Weighted Imaging Improves the Diagnostic Accuracy of 3T Brain MRI in the Work-Up of Parkinsonism

Abstract: BACKGROUND AND PURPOSE:The differentiation between Parkinson disease and atypical parkinsonian syndromes can be challenging in clinical practice, especially in early disease stages. Brain MR imaging can help to increase certainty about the diagnosis. Our goal was to evaluate the added value of SWI in relation to conventional 3T brain MR imaging for the diagnostic work-up of early-stage parkinsonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 42 publications
0
65
0
2
Order By: Relevance
“…Decreased putaminal hypointensity using SWI reflecting increased iron levels in MSA-P vs. PD was also reported by other reports (Lee and Baik 2011; Han et al 2013). Decreased mean SWI signal intensities of the red and dentate nuclei were reported to occur in patient with PSP compared to PD patients in one study (Meijer et al 2015a), while another reported decreased mean SWI signal intensities in the red nucleus and putamen. Mean phase shift values in different subcortical regions (including red nucleus, SN, caudate nucleus, globus pallidus, putamen, and thalamus) were analysed in a further study of 11 patients with PSP, 12 patients with MSA-P, 15 patients with PD, and 20 controls.…”
Section: Exclusion Of Alternative Diagnosesmentioning
confidence: 97%
See 3 more Smart Citations
“…Decreased putaminal hypointensity using SWI reflecting increased iron levels in MSA-P vs. PD was also reported by other reports (Lee and Baik 2011; Han et al 2013). Decreased mean SWI signal intensities of the red and dentate nuclei were reported to occur in patient with PSP compared to PD patients in one study (Meijer et al 2015a), while another reported decreased mean SWI signal intensities in the red nucleus and putamen. Mean phase shift values in different subcortical regions (including red nucleus, SN, caudate nucleus, globus pallidus, putamen, and thalamus) were analysed in a further study of 11 patients with PSP, 12 patients with MSA-P, 15 patients with PD, and 20 controls.…”
Section: Exclusion Of Alternative Diagnosesmentioning
confidence: 97%
“…Patients with atypical parkinsonism due to PSP and MSA often show putaminal changes using iron-sensitive MRI sequences to a degree that they are of significant diagnostic yield (Arabia et al 2010; Gupta et al 2010; Haller et al 2012, 2013; Wadia et al 2013; Feng et al 2015; Meijer et al 2015a; Yoon et al 2015; Barbagallo et al 2016; Sakurai et al 2017). SWI phase images were applied for the determination of different iron-deposition patterns in several grey nuclei in 16 patients with PD, 8 patients with MSA-P and 44 age-matched healthy controls (Wang et al 2012b).…”
Section: Exclusion Of Alternative Diagnosesmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was not clearly indicated by previous imaging studies, even those that used 3T imaging or 3T SWI. 18,23 Our quantitative measurement method was not a volumetric method and did not include all putaminal areas or consider the high-iron-deposition area that was proposed to be meaningful by previous publications. 11,13 Haacke et al 11 demonstrated that putative iron deposition in the high-iron-content region increases with age.…”
Section: Discussionmentioning
confidence: 99%